Experimental study on optical fiber bundle hydrogen sensor based on palladium-silver optical thin film - 崔陆军 尚会超 张冈 李勇 赵则祥 (Optoelectronics letters, 2013)
In this paper, a 20 nm palladium-silver （Pd/Ag） ultrathin optical film is used for hydrogen gas sensing. The mole ratio of the two metals is controlled at Pd：Ag=3：1. In the direct current （DC） sputtering machine, the optical thin film is evaporated on the optical glass. Compared with pure palladium, the Pd/Ag alloy can increase the life and the stability of the sensing film. Optimum sputtering parameters for Pd/Ag alloy are presented in this paper, and the effects of different experimental condi- tions for hydrogen sensor are investigated, including the temperature effect, humidity effect and cross sensitivity of hydro- gen sensor for different gases. The experiment results indicate that the hydrogen sensor based on Pd/Ag optical thin film exhibits good sensing characteristics. The existing of CO and water in hydrogen increases the response time and decreases the response amplitude of optical fiber bundle hydrogen sensor. The experiment results show that the increasing tempera- ture can eliminate the effect and shorten hydrogen sensor response time effectively.